Voice at the interfaces : The syntax, semantics, and morphology of the Hebrew verb - Kastner, Itamar (Language Science Press, 2020)
This books presents the most comprehensive description and analysis to date of Hebrew morphology, with an emphasis on the verbal templates. Its aim is to develop a theory of argument structure alternations which is anchored in the syntax but has systematic interfaces with the phonology and the semantics. Concretely, the monograph argues for a specific formal system centered around possible values of the head Voice. The formal assumptions are as similar as possible to those made in work on non-Semitic languages. The first part of the book (four chapters) is devoted to Hebrew; the second part (two chapters) compares the current theory with other approaches to Voice and argument structure in the recent literature.
English
Keywords: linguistics; Biography: general; Language Arts & Disciplines; Linguistics; Biography & Autobiography